Assessing the Performance of the Developing Countries for the Utilization of the Green Climate Fund - Ari, Izzet; Isik, Mine (Frontiers in Climate, 2022)
Emission mitigation actions are being undertaken at the global level to combat climate change and address potential climate risks. The Green Climate Fund (GCF) is a major source of finance to catalyse the transformation towards a low emission future in developing countries. While the importance of the GCF is widely acknowledged, quantitative evaluation of its utilization is limited. Using data envelopment analysis (DEA), the aim of this study was to perform an empirical analysis of the differences in the relative efficiency of countries regarding the implementation of the GCF on emission mitigation projects. In line with the structure of green climate funding, three performance indicators were identified as input parameters, monetary leverage effect of GCF, political environment and Research and Development (R&D) spending. Data were collected for 30 countries that received GCF. Those countries were clustered as the least developed countries (LDC), small island developing states (SIDS) and other developing countries. The findings of this study indicated that Mauritius, Lao, and Congo fully utilized the funding they received and showed satisfactory performance within the LDC and SIDS countries. Vietnam, Pakistan, Nigeria and Ecuador were also found to be the efficient frontiers among other developing countries. These results presented that decision making tools and processes should be considered to increase the efficiency level of utilization of the GCF for emissions reduction in developing countries.